Zdrowie psychiczne w czasie pandemii – perspektywa studentów z niepełnosprawnościami - Gutowska, Anna (Życie z niepełnosprawnością w świecie VUCA, 2022)
The Authors present the results of their study performed on a group of Polish university students. The students represented varied disabilities. The research was conducted during COVID-19 pandemics after the period of distance education. The findings concentrate on psychosocial aspect of functioning of students with disabilities during the crisis situation caused by pandemics. The research also provides an insight into the students’ selfassessment of their psychophysical condition during obligatory isolation. The authors discussed students’ expectations concerning support from the university and the one that they actually received. The conclusions from the research enabled formulating recommendations for university student support units.